Development of profilactic work in fire fire safety - Andriienko, M.; Shoiko, V. (Ways to Improve Construction Efficiency, 2018)
The article deals with the main directions of development of preventive work in the field of fire safety. The causes of the fires in enterprises, organizations and institutions in Ukraine are highlighted. Proposed measures for the implementation of preventive work to prevent the violation of rules and regulations of the fire department.